Penerapan Model Round Table dengan Flash Card pada Pembelajaran Aksara Jawa Kelas IV di SD Negeri 1 Pepedan - Fitriani Retno Wardani (Yayasan Bina Nagari Banyumas, 2025)
This research is motivated by the low reading and writing skills of Javanese scriptin grade IV students at SD Negeri 1 Pepedan. This problem arises because of the lowinterest of students in learning, difficulty in remembering the form of letters, andthe use of learning media that are less interesting. To overcome this, the teacherapplies the Round Table learning model with the help of flash card media to increasestudent activity and facilitate mastery of Javanese script material. The purposeof this study is to describe how the Round Table model is applied with flash cardmedia in learning Javanese script in grade IV of SD Negeri 1 Pepedan. This studyuses a qualitative descriptive approach with data collection techniques throughobservation, interviews, and documentation. The validity of the data is obtainedthrough triangulation of sources and techniques. The results of the study indicatethat the application of the Round Table model with flash cards includes three stages, namely: (1) the planning stage, which includes the preparation of teaching modules, media preparation, and student readiness; (2) the implementation stage, whichconsists of apperception activities, introduction to basic letters and sandhangan,group discussions, reading and writing exercises, taking turns working on questions,and group presentations; and (3) evaluation stage, in the form of written and oraltests. Supporting factors for the implementation of this model include active teacherinvolvement, suitability of the model and media to the material, and positiveresponses from students. Inhibiting factors include differences in students’ academicabilities, time constraints, and insufficient flash card media.